STAN BADAŃ NAD DZIEJAMI PUSZCZY KAMPINOSKIEJ - Sukiennik, Edgar (Saeculum Christianum. Pismo Historyczne, 2017)
Kampinos Forest, also known as the Kampinos National Park, is a large forest complex located north-west of Warsaw. This is a unique natural heritage resource full of various forms of wildlife and many types of animals. In this remarkable natural monument are also to be found traces of human activity. Forest areas remained untouched for a long time, but since the 15th century people have begun the first settlements and villages. Within a few hundred years there has been created in this area many towns, parishes and centers of agricultural and forestry. During the Polish uprisings of the 19th and 20th centuries, the forest terrain was favorable to guerilla actions and is now a place of burial for several thousand people who are buried in military cemeteries. These topics were studied by historians, who wanted and still want to show the area of human activity and the evolution of the relationship between nature and man. The Kampinos Forest is seen in many publications as the place for daily life of inhabitants from the Middle Ages to the present day. This article is an attempt to discuss the current trends of historical research in this part of Mazovia. It also shows the perception of events by the authors. The issues of nature, landscape formation, geological processes and environmental protection are not included, because they belong to other fields of science and have a separate research methodology.